How Pakistan Got Divided - Farman Ali, Khan Rao (Maj. Gen. Retd) (New York Oxford University Press, 2017)
The book is an eyewitness account of the events that led to a civil war in East Pakistan, which culminated in the creation of Bangladesh. It is written by Major General Rao Farman Ali Khan, a well-known army officer present in the Eastern Wing during the war of 1971. His experience of the Eastern Wing spanned almost five years; in the latter three years (196971), he held the key appointment of Advisor on Civil Affairs to the Governor of East Pakistan. By virtue of this role, and the length of his tenure in East Pakistan, he acquired deep insight and knowledge of the political and military events as they unfolded. In this candid account, Rao Farman Ali brings to light the political undercurrents and aspects of the military conflict generally not known. His personal interactions with both, the Bengali and West Pakistani politicians, as well as the military commanders, gave him a unique vantage point to analyse the events and decisions taken that led to the fateful day 16 December 1971 the division of Pakistan.
Includes Illustrations, Appendix and Index.
Keywords: Pakistan -- Politics and Government -- War--Causes